ANALISIS PELAYANAN JASA PENGIRIMAN DAN PENERIMA PADA J&T CABANG RABA BIMA - MUH FURKAN RAMADHAN; MUHAJIRIN MUHAJIRIN (GANEC SWARA, 2024)
The aim of this research is to find out the Delivery and Recipient Services at J&T Raba Bima Branch. The research method used in this study is a descriptive research method. The research instrument used a questionnaire with a Likert scale. The population in this study is consumers who have used delivery and receiving services at J&T Raba Bima Branch. The sample in this study was as many as 50 respondents using the slovin formula with an acidental sampling technique. The data collection techniques used are observation, questionnaire and literature study. The data analysis techniques used were validity tests, reliability tests, descriptive analysis and t tests (t test one sample). The results of the study show that the delivery and receiving services at J&T Raba Bima Branch are equal to 70% of what was expected (good).